CELEBRITY ENDORSEMENT AND BRAND IMAGE ON INSTAGRAM ON ZOYA'S HIJAB PURCHASE DECISION: A STUDY ON UMT STUDENTS - Utomo, Eko Narto; Hasan, Muh; Astuti, Teri (Dynamic Management Journal, 2025)
The development of social media, especially Instagram, has changed the marketing strategy of Muslim fashion products among the younger generation. The phenomenon of using celebrity endorsements and strengthening brand image is an important factor in shaping consumer purchase decisions. This study aims to analyze the influence of Instagram social media, celebrity endorsements, and brand image on the decision to purchase Zoya hijab among female students of the University of Muhammadiyah Tangerang. The research method used was quantitative with a survey approach, involving 95 seventh-semester female student respondents. Data analysis was carried out through the stages of validity, reliability, classical assumption, multiple linear regression, and hypothesis test using SPSS version 26. The results of the study show that the three independent variables partially or simultaneously have a positive effect on purchasing decisions. These findings contribute to the digital marketing literature and consumer behavior, especially in the context of Muslim fashion. The novelty of this research lies in the integration between social media platforms, public figures, and brand perceptions in shaping purchasing decisions in the student segment, which is still rarely explored empirically in the local context